2003
DOI: 10.1046/j.1365-2990.2003.00459.x
|View full text |Cite
|
Sign up to set email alerts
|

Misrouted olfactory fibres and ectopic olfactory glomeruli in normal humans and in Parkinson and Alzheimer patients

Abstract: The presence and distribution of misrouted (MR) olfactory projection fibres were studied in the olfactory bulbs of control human brains and in the brains of people who had suffered from Parkinson's and Alzheimer's disease. It appeared that MR fibres, that is, fibres that terminate deep into the glomerular layer, are a common phenomenon in the bulbs of aged people. In all but one of the bulbs studied, MR fibres are present. The amount of MR fibres is not related to age. With a few exceptions, the MR fibres are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 23 publications
3
23
0
1
Order By: Relevance
“…The familiarity score for the odorants was significantly higher on the OSIT-J than on the CC-SIT. Kobayashi et al (30) (20,34,35 (14).…”
Section: Co Mp a R I S O N B E T We E N T H E Un I F I E D P A R K mentioning
confidence: 99%
“…The familiarity score for the odorants was significantly higher on the OSIT-J than on the CC-SIT. Kobayashi et al (30) (20,34,35 (14).…”
Section: Co Mp a R I S O N B E T We E N T H E Un I F I E D P A R K mentioning
confidence: 99%
“…12 A recent study demonstrated that olfactory dysfunction in PD is related to atrophy in olfactoryeloquent regions of the limbic and paralimbic cortices. 13 These olfactory deficits have been linked to structural and/or functional changes at the level of the OB 9,12,14,15 and OS. 16 There is evidence from numerous studies that MR imaging can be used to reliably evaluate the volume of the OB and the depth of OS.…”
mentioning
confidence: 99%
“…As a matter of fact, hyposmia or anosmia develop as preclinical signs in PD patients. 3,4 This deficit has also been related to structural and/or functional changes at the level of the olfactory bulb, e.g., including misrouted axonal terminals of olfactory receptor neurons that form glomerulus-like structures 3 or signs of neuroinflammation and microgliosis.…”
mentioning
confidence: 99%